Utilização da levedura alcoólica (Sacharomy cerevisae) como fonte protéica na alimentação de juvenis de pacu (Piractus mesopotamicus, Pisces, Teleostei): aspectos metabólicos e de desempenho produtivo - Pádua, Delma Machado Cantisani [UNESP] (1996)
The present experiment assessed the effect of inclusion of different levels of the single cell protein molasses yeast (Saccharomyces cerevisiae) in the diet of juvenile pacu (Piaractus mesopotamicus) replacing fish meal. Five isoproteic (26 % CP) and isocacloric (4000 kcal GE/kg) diets were formulated in which the levels of substitution by yeast were 25, 50, 75 and 100 % and tested in two periods, following a Split Plot in Time design. Diets were fed twice a day ad libitum. Two hundred fish were allotted in 20 cement tanks of 1330 l, with continuous water flow, and sampled at 45 and 87 days after start feeding. It was possible to include until 75 % of molasses yeast in substitution of fish meal without negative effects in the parameters analyzed. The highest level of yeast in the diet (100 %) showed delayed growth, with low specific growth rate and did not affected significantly the body composition, excepting for higher mineral content. The same level of yeast provoked high mortality of fish. Its was observed hyperglycemia and decrease in liver glycogen, total liver lipid content and plasma protein in fish fed on diet containing 100 % molasses yeast. Following the same pattern of response hepatocytes showed the lowest area and volume of cytoplasm, at the same treatment. Increase in hematocrit levels appeared at 100 % molasses yeast diet only at 87 days. The other molasses yeast diets (25, 50 and 75 %) presented similar performance compared to control diet. Concluding, the results of the present study suggest that the diet with total replacement of fish meal by molasses yeast showed an antinutritional effect